2005
DOI: 10.1063/1.1940138
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of hydrogenated amorphous carbon deposits from electron-beam-induced deposition of a paraffin precursor

Abstract: Many experiments on the mechanics of nanostructures require the creation of rigid clamps at specific locations. In this work, electron-beam-induced deposition ͑EBID͒ has been used to deposit carbon films that are similar to those that have recently been used for clamping nanostructures. The film deposition rate was accelerated by placing a paraffin source of hydrocarbon near the area where the EBID deposits were made. High-resolution transmission electron microscopy, electron-energy-loss spectroscopy, Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
162
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(181 citation statements)
references
References 49 publications
14
162
0
Order By: Relevance
“…Below, we demonstrate the proposed behavior using a model of simultaneous etching and deposition. In the model, we eliminate the effects of precursor molecule surface diffusion and of the beam revisit period 31,50,51 by considering the case of an electron-irradiated semi-infinite surface. We assume that both etch and deposit precursors arrive from vacuum, with arrival rates determined by their respective partial pressures.…”
Section: Theory and Discussionmentioning
confidence: 99%
“…Below, we demonstrate the proposed behavior using a model of simultaneous etching and deposition. In the model, we eliminate the effects of precursor molecule surface diffusion and of the beam revisit period 31,50,51 by considering the case of an electron-irradiated semi-infinite surface. We assume that both etch and deposit precursors arrive from vacuum, with arrival rates determined by their respective partial pressures.…”
Section: Theory and Discussionmentioning
confidence: 99%
“…TEM observation revealed that the layer thickness ranged from 1-10 nm. According to our previous work [36], the deposit consists of hydrogenated amorphous carbon having an elastic modulus roughly in the range 30-60 GPa. If the EBID deposit is also bearing load, the tensile stress supported by the outermost shell is overestimated in our analysis, and thus the strength and modulus values would be as well.…”
Section: Tensile Stress Calculationmentioning
confidence: 99%
“…In order to avoid nanowire sliding during the bending tests, both ends of the nanowires, which bridged the channel, were clamped by electron-beaminduced deposition ͑EBID͒ of carbonaceous materials ͑paraffin͒. 36 A Veeco Dimension 3100 AFM was used to perform three-point bending tests by directly indenting the center of a suspended nanowire which bridged the channel with a tapping mode silicon AFM tip. Figure 1͑a͒ shows the SEM image of the as-grown SiO 2 nanowires.…”
mentioning
confidence: 99%